The Intervention of Trunk Posture on Fowler 30o to Reduce Shortness of Breath in Congestive Heart Failure Patients : Case Study - Anggi Jamiyanti; Sarah Arnika Simatupang; Trias Eka Nurlela; Eka Afrima Sari; Yusshy Kurnia Herliani; Ramdani Ramdani (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2022)
ABSTRACTIntroduction: Shortness of breath in patients with congestive heart failure is caused by impaired lung function due to pulmonary. One of the efforts that can be done to overcome shortness of breath and improve oxygenation status is to change the position of the trunk posture in fowler 30o. Objectives: This case study was conducted to analyze the application of the 30o trunk posture in fowler position in patients with congestive heart failure who experience shortness of breath. Method: The research used a a case study of patients with congestive heart failure who experience shortness of breath. Results: After giving a 30o trunk posture in fowler position for three days of treatment, there was a change of blood pressure, pulse rate, respiration and oxygen saturation of the patient. Conclussion: The position of the trunk in fowler posture 30o can reduce shortness of breath in patients with congestive heart failure.ABSTRAKPendahuluan: Sesak nafas pada penderita gagal jantung kongestif disebabkan oleh terganggunya fungsi paru karena adanya edema pulmonal. Salah satu upaya yang dapat dilakukan untuk mengatasi sesak nafas dan memperbaiki status oksigenasi adalah dengan mengubah posisi trunk posture in fowler 30o. Studi kasus ini dilakukan untuk menganalisis penerapan posisi trunk posture in fowler 30o pada pasien gagal jantung kongestif yang mengalami sesak nafas. Metode: Penelitian ini menggunakan desain evaluatif yaitu studi kasus pada pasien dengan kongestif heart failure dengan sesak nafas. Hasil: Setelah dilakukan oberservasi pemberian posisi trunk posture in fowler 30o selama 3 hari perawatan, terdapat perubahan tekanan darah, denyut nadi, pernafasan dan saturasi oksigen pasien. Simpulan: Posisi trunk postur in fowler 30o dapat mengurangi sesak napas pada pasien gagal jantung kongestif.